Containing a measles outbreak in Minnesota, 2017: methods and challenges. (May 2020) - Banerjee, E; Griffith, J; Kenyon, C; Christianson, B; Strain, A; Martin, K; McMahon, M; Bagstad, E; Laine, E; Hardy, K; Grilli, G; Walters, J; et al.
Aims: We report on a measles outbreak largely occurring in Minnesota's under-vaccinated Somali community in the spring of 2017. The outbreak was already into its third generation when the first two cases were confirmed, and rapid public health actions were needed. The aim of our response was to quickly end transmission and contain the outbreak. Methods: The state public health department performed laboratory testing on suspect cases and activated an Incident Command staffed by subject matter experts that was operational within 2 h of case confirmation. Epidemiologic interviews identified exposures in settings where risk of transmission was high, that is, healthcare, childcare, and school settings. Vaccination status of exposed persons was assessed, and postexposure prophylaxis (PEP) was offered, if applicable. Exposed persons who did not receive PEP were excluded from childcare centers or schools for 21 days. An accelerated statewide measles, mumps, and rubella (MMR) recommendation was made for Somali Minnesota children and children in affected outbreak counties. Partnerships with the Somali Minnesota community were deepened, building off outreach work done with the community since 2008. Results: Public health identified 75 measles cases from 30 March to 25 August 2017: 43% were female, 81% Somali Minnesotan, 91% unvaccinated, and 28% hospitalized. The median age of cases was 2 years (range: 3 months–57 years). Most transmission (78%) occurred in childcare centers and households. A secondary attack rate of 91% was calculated for unvaccinated household contacts. Over 51, 000 doses of MMR were administered during the outbreak above expected baseline. At least 8490 individuals were exposed to measles; 155 individuals received PEP; and over 500 persons were excluded from childcare and school. State and key public health partners spent an estimated $2.3 million on response. Conclusion: This outbreak demonstrates the necessity of immediate, targeted disease control actions and strong public health, healthcare, and community partnerships to end a measles outbreak.